Handbook on measurement, assessment, and evaluation in higher education - Secolsky, Charles; Denison, D. Brian (New York, NY : Routledge, 2012)
"Increased demands for colleges and universities to engage in outcomes assessment for accountability purposes have accelerated the need to bridge the gap between higher education practice and the fields of measurement, assessment, and evaluation. The Handbook on Measurement, Assessment, and Evaluation in Higher Education provides higher education administrators, student affairs personnel, institutional researchers who generate and analyze data, and faculty with an integrated handbook of theory, method, and application. This valuable resource brings together applied terminology, analytical perspectives, and methodological advances from the fields of measurement, assessment, and evaluation to facilitate informed decision-making in higher education. Special Features: Contributing Authors are world-renowned scholars across the fields of measurement, assessment, and evaluation, including: Robert E. Stake, Trudy W. Banta, Michael J. Kolen, Noreen M. Webb, Kurt Geisinger, Robert J. Mislevy, Ronald K. Hambleton, Rebecca Zwick, John Creswell, and Margaret D. LeCompte. Depth of Coverage includes classroom assessment and student outcomes; assessment techniques for accountability and accreditation; test theory, item response theory, validity and reliability; qualitative, quantitative and mixed-methods evaluation; context and ethics of assessment Questions and Exercises follow each Section to reinforce the valuable concepts and insights presented in the preceding chapters. Bridging the gap between practice in higher education with advances in measurement, assessment, and evaluation, this book enables educational decision-makers to engage in more sound professional judgment. This handbook provides higher education administrators with both high-level and detailed views into contemporary theories and practices, supplemented with guidance on how to apply them for the benefit of students and institutions"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Education, Higher -- Evaluation -- Handbooks, manuals, etc; Educational tests and measurements -- Handbooks, manuals, etc; EDUCATION / General